Peningkatan Iman dan Moral Anak Melalui Pembelajaran Aqidah Akhlak - Agus Hasan Mustofa (STID Raudlatul Iman Sumenep, 2020)
The age of globalization characterized by advances in science and technology coming to Indonesia is irreversible, its presence is not only a positive impact as such, but also had a negative impact, a negative impact on children is diminishing belief to things spiritually like faith God, angels, books, messengers, the Last day and qada ', Qadr. In addition, today's children also experienced the decadence like daring to parents, no disrespect to the older, daring to teachers. Small picture of a child's life in modern times need serious attention, including by educational institutions especially the role of Islamic religious teachers as someone who took on the task of educating the nation and improve morale through the learning material to learners' aqidah morals. Zaman globalisasi yang ditandai dengan kemajuan ilmu pengetahuan dan teknologi tidak dapat dibendung lagi. Selain membawa dampak positif, kehadirannya juga membawa dampak negatif. Salah satu dampak negatif globalisasi yang menimpa anak adalah menipisnya kepercayaan anak terhadap hal-hal yang bersifat spirituil, seperti iman kepada Allah, malaikat, kitab-kitab, rasul-rasul, hari akhir, dan qada’, qadar. Selain itu, anak-anak zaman sekarang juga mengalami dekadensi moral seperti berani kasar kepada orang tua, kurang respek kepada yang lebih tua, dan hilangnya rasa takdzim kepada guru. Gambaran kecil kehidupan anak di zaman modern ini perlu mendapat perhatian yang serius termasuk oleh lembaga pendidikan Islam terutama peran guru agama sebagai sosok yang mengemban tugas untuk mencerdaskan kehidupan bangsa dan memperbaiki moral melalui materi pembelajaran aqidah akhlak kepada peserta didiknya.